Penegakkan Hukum Penyalahgunaan Narkotika Oknum Pegawai BNN Provinsi Lampung - Pratama, Lollyandi; Saravistha, Deli Bunga (Jurnal Indragiri Penelitian Multidisiplin, 2024)
Drug abuse by several officials of the National Narcotics Agency (BNN) in the Province of Lampung has become a serious issue that affects the image of law enforcement agencies and has a negative impact on society. The alleged abuse involves not just ordinary civilians, but a viral case involving Fredy Pratama. It was in the online news media metrotv news that Lampung Police arrested an honorary member of the Lampung National Narcotics Agency (BNN) named M.Y. According to Kapolda Lampung Irjen Helmy Santika, MY, who is 26 years old, serves as a courier who ships drugs of the type Fuj-sabu. He stated that M.Y was arrested on January 14, 2024 at Bakauheni Executive Port with 28 packages of drugs. The research method used is normative. The results show that working environment factors, social stress, and a lack of internal supervision contribute to drug abuse. Effective preventive efforts include improved surveillance, rehabilitation programmes, and sustained education for BNN staff. BNN also held an internal seminar to give an understanding of the gravity of the punishment for drug abuse perpetrators. At the local level, initiatives such as the inauguration of the Drug-Free Hard Village in Sukaraja Kelurahan show concrete steps in prevention efforts. The village was chosen on the basis of increasing data on drug abuse cases, and is expected to be an example for other areas in creating a drug-free environment. Drug abuse among civil government officials (PNS) is also a concern. Factors such as the living environment and free association are often the main triggers. The preventive efforts included socialization on the dangers of drugs and periodic urine tests to detect drug abuse among the PNS. There are three ways to combat crime, mainly narcotics abuse, namely pre-emtive (planning), preventive (prevention), and repressive.